Differences in Knowledge of Young Women About Early Marriage and Pregnancy at a Young Age Pre and Post Counseling In MAN 4 Kab. Tangerang - Sintha Wijayanti (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Teenage pregnancy occurs between the ages of 14-19 years. The number of those who married early before the age of 18 in 2018 puts Indonesia in the 10 countries with the highest absolute number of child marriages in the world, which is estimated at around 1,220,900. According to the UNFPA report, globally every year it is estimated that 14 million adolescents aged 15-19 years give birth and more than 90% of these births occur in developing countries. This study aims to determine the differences in young women’s knowledge about early marriage and pregnancy at a young age before and after counseling at MAN 4 Kab. Tangerang. This study uses quantitative methods and designs, namely